Age-specific prevalence of erosive tooth wear by acidic diet and gastroesophageal reflux in Japan. Issue 4 (April 2015) - Kitasako, Yuichi; Sasaki, Yoshiyuki; Takagaki, Tomohiro; Sadr, Alireza; Tagami, Junji
Abstract Objectives To evaluate the age-specific prevalence of erosive tooth wear in Japanese adults. Methods The study sample consisted of a total of 1108 adults aged 15–89 yrs in Tokyo, Japan. The subjects were asked to complete a self-administered nutrition-related questionnaire. Two examiners evaluated tooth wear in a full-mouth recording, using a modified tooth wear index developed based on the Smith and Knight Tooth Wear index. Subjects who had frequent acid consumption or gastric reflux and at least one tooth with an initial enamel wear were placed in an erosive wear positive group, and the rest of subjects were placed in the erosive wear negative group. Results The median (IQR) prevalence of erosion was 19.1 (1.8) at enamel level and 6.5 (3.7) with dentin exposure. There were statistical differences in prevalence of erosive wear among different age groups (p < 0.05). Dietary habits found to be frequent in erosive wear positive group included acidic juices for younger subjects (15–39 yrs), and acidic fruits for older subjects (60–89 yrs). The prevalence of gastroesophageal reflux and eating disorder was 3.5%. A severe loss of dental tissue was observed on labial and incisal surfaces of anterior teeth in the erosive wear positive group. Conclusions In the studied sample of Japanese adults, 26.1% had signs of erosive wear. Clinical significance Erosive wear, in combination with abrasion and attrition, results in severe loss of tooth tissue. Frequent consumption of acidic fruits and drinks was significantly associated with erosive tooth wear at different age groups.